Comparison of maximum likelihood, support vector machines, and random forest techniques in satellite images classification - José Antonio Valero Medina; Beatriz Elena Alzate Atehortúa (Tecnura, 2019)
Context: Nowadays, the images of the Earth surface and the algorithms for their classification are widely available. In particular, the algorithms are promising in the differentiating of cotton crops stages, but it is necessary to establish the capabilities of the different algorithms in order to identify their advantages, and disadvantages.